MERANCANG ANATOMI PENGELOLAAN HUTAN OLEH MASYARAKAT DESA - Rifan, Mohamad (PANGRIPTA, 2019)
the problem of forest, law, and community mirrors that the development of forest product commodities cannot be separated from the historical sequence of forest management in Indonesia which is a portrait of structural transformation between the community and the government of forest resources which is projected as an effort to realize ideal forest management. This condition is an initial task for the state and all its components to develop a forest management framework, which means it cannot be separated from the authority of the government which includes the village community, as well as the forest itself. Through normative juridical research methods, this paper will focus on anatomical discussions of forest management that are carried out when involving rural communities in the regions. the results of this study explain that: First, the beginning of the anatomy of forest management begins with a shift in forest management patterns. Second, the village community is one of the elements in the anatomy / management of the forest because of the strong relationship to forest resources in terms of concepts, norms, and history. Third, the anatomical framework of forest management is influenced by the Government, Village Communities and Forests as an interrelated system.